Human Capital and Economic Growth in Pakistan (Distinguished Lecture) (The Pakistan Development Review, 2005)
Pakistan’s economy has grown faster on average than many other low- and middleincome countries over the past two decades. But several countries in Southeast Asia have fared even better. This paper focuses on factors that explain Pakistan’s relative growth performance. In addition to more traditional factors believed to determine growth, this paper looks particularly at the role of differences in the quality of human capital. The cross-country empirical results suggest that accumulation of physical capital and improvements in the quality of institutions have the largest pay-offs in terms of achieving higher growth, but that better education and health care also have a significant impact. Investment in these areas will increase the possibility of Pakistan entering a virtuous cycle of high growth and improved living conditions for the population.